Developing and applying a socio-ecological model to the promotion of healthy eating in the school. - Townsend, N; Foster, C (2013)
OBJECTIVE: To develop and apply a socio-ecological model (SEM) for healthy eating in school students, to better understand the association between factors at different levels of the SEM and pupils' dietary choices. DESIGN: Student-level data, collected through anonymised questionnaires, included reported dietary choices and correlates to these; data on school approaches to food were collected through postal surveys. We used multilevel analysis to study the association of each level of the SEM on student dietary choice while controlling for factors found at other levels. SETTING: Data were collected from secondary schools in Wales that were a part of the 2005/2006 Health Behaviour in School-aged Children (HBSC) study. SUBJECTS: The final sample for analysis included data from 6693 students aged 11-16 years and 289 teachers from sixty-four secondary schools in Wales. RESULTS: Student interpersonal factors, an individual's social environment, had a greater association with the dietary choices students made for lunch than student intrapersonal characteristics, those that reside within the person, which were found to have a greater association with the dietary choices made outside school. School organisational factors, such as rules and policies, had a greater association with whether students ate unhealthy foods, whereas the community nature of the school had a greater association with the choosing of healthy foods. CONCLUSIONS: Using the SEM and multilevel analysis allowed us to study how factors were associated with the choice of different foods at different times of the day by students. Interventions can use an SEM to target specific correlates and change health outcomes in the school.